Hypoglycemia in sick and moribund farmed elk calves - Klein, Kristie A. (2002)
Blood glucose was found to be below the reference range in most farmed elk calves examined at the Western College of Veterinary Medicine teaching hospital. Hypoglycemia was associated with diarrhea, sepsis, and malnutrition. Blood glucose analysis and, when indicated, intravenous dextrose administration are recommended when treating moribund farmed elk calves.